1998
DOI: 10.1002/(sici)1096-8652(199803)57:3<193::aid-ajh2>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of plasma prothrombin and factor VII and urine prothrombin F1 concentrations in patients on long-term warfarin therapy and those in the initial phase

Abstract: Control of warfarin anticoagulation during the initial phase of therapy is difficult and empirically based. Plasma and urine samples were obtained from normal controls, patients under stable anticoagulation, and patients in the initial phase of anticoagulation. Total plasma prothrombin, des-carboxy (non-adsorbable with barium chloride) prothrom-bin, and native (total minus non-adsorbable) prothrombin were quantitated using Echis carinatus venom activation. Functional plasma factor VII (VII) was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(39 reference statements)
0
15
0
Order By: Relevance
“…Coumarins depress the plasma levels of FVII, FX, and prothrombin to differing degrees, ranging from about 10–40% of normal in therapeutically anticoagulated patients [12,13,25–29]. To better compare thromboplastin properties using clotting factor deficiencies spanning the therapeutic range, we replotted PT ratio data from Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Coumarins depress the plasma levels of FVII, FX, and prothrombin to differing degrees, ranging from about 10–40% of normal in therapeutically anticoagulated patients [12,13,25–29]. To better compare thromboplastin properties using clotting factor deficiencies spanning the therapeutic range, we replotted PT ratio data from Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Even in stably anticoagulated patients, the plasma levels of FVII, FX, and prothrombin may be depressed to different degrees [25–28]. Some studies have attempted to correlate the plasma activities of single coagulation factors with INR values from individual patients, variously concluding that INR correlates best with deficiency in FVII [12,25], a combination of FVII and prothrombin deficiency [29], or native prothrombin [35]. Our results suggest that differences in the apparent contributions of individual clotting factors to INR may result from using thromboplastins with differing relative sensitivities to FVII, FX, and prothrombin.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thus, even when identical INR values are measured, the plasma concentration of these coagulation factors may greatly vary between induction and stable anticoagulation within the same patient. In the study by Weinstock et al [35], plasma levels of factors II and VII were compared in the initial phase of warfarin treatment and during long-term anticoagulation therapy. Both factors significantly correlated with INR in both phases.…”
Section: Discussionmentioning
confidence: 99%
“…Technically, they developed an antibody versus fully carboxylated native prothrombin which was applied in a radioimmunoassay. Weinstock et al (10) used barium ion absorption for isolating and differentiation of native vs. non-carboxylated prothrombin. They compared stably vs. initially anticoagulated patients and found that native prothrombin correlates with 1/INR in both groups, but for any given INR, the concentration among stably anticoagulated patients is significantly lower than among patients in the initial phase.…”
mentioning
confidence: 99%